Pengembangan Movable Book untuk Meningkatkan Keterampilan Proses Sains Siswa - Syafutri, Ridha; Soeharto, Soeharto (JPI (Jurnal Pendidikan Indonesia), 2019)
Abstract: Books become a source of student activity and experience, serve as a guide for exploration, and experiment with concrete materials, directing students to be involved in the process and method of inquiry. The book provides direction for direct science experiences. This study aims to develop a feasible and effective movable book to improve students' science process skills. This study was a development research with Borg and Gall development model. The subjects were students and teachers of grade IV elementary school in Ngaglik sub-district Yogyakarta. Data collection was carried out through questionnaires and tests. Validation of products developed was carried out by media experts, and material experts. Teacher responses and responses of students were asked to see the practicality of using the product. Based on the validation, it was known that the movable book was feasible for use. Feasibility in the media aspect obtained a score of 255 with the category "feasible", the material aspect obtained a score of 95 with the category "feasible". The acquisition of teacher response scores from 109 to 116 with the category "very feasible", the acquisition of student response scores from 35 to 37.95 with the category "very feasible". The product that was developed effectively improved the science process skills based on the results of independent sample t-test showed a significance level of 0.03 which means